Activities workshop: Giving attention to disabled children family - Baleotti, Luciana Ramos [UNESP]; Omote, Sadao [UNESP]; Gregorutti, Carolina Cangemi [UNESP] (Universidade Estadual de Maringa, 2015)
The aim of this study was to identify the perception of caregivers of disabled children regarding their experience in activities workshop. It is a longitudinal study involving nine primary caregivers of children with disabilities. The caregivers participated in ten group meetings, once a week, to carry out different activities. Two procedures were used for data collection. At the beginning and at the end of each meeting, the participants chose one of three figures, representing three facial expressions corresponding to feelings of happiness, sadness and intermediate emotional state. By means of the choice of an illustration, the participants expressed their feelings on that day. The choice was justified by the end of each meeting. An individual semi-structured interview was carried out by the closing of the ten meetings. The results suggest that the participation in the group provided moments of pleasure, creativity and temporary distancing in relation to the disabled children's care. Besides, the strengthened of new friendships beyond the moments enjoyed in the group. The results of this study can be useful to the health professionals who are working with disabled children, aiding them in the intervention process that not only considers the health conditions of these children, but also who are routinely linked to them, their caregivers.
Keywords: Disability; Family; Workshop activity